2021
DOI: 10.1007/s13346-021-00989-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-luminescent photodynamic therapy and pathogen detection for infectious diseases

Abstract: The importance of detection and treatments of infectious diseases has been stressed to the world by the ongoing COVID-19 pandemic. As a substitution of an external light source, self-luminescent therapeutics featuring in situ light emission aims to address the lack of tissue penetration in conventional photodynamic therapy (PDT). Luminol-based self-luminescent systems are successfully incorporated in PDT and detection of pathogens in infectious diseases. In these systems, luminol/hydrogen peroxide is served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…ere were no cases of missed diagnosis or underreporting of infected patients, and no cases of nosocomial infection or cross-infection during the implementation of the normalized management model. By strengthening skills training and psychological interventions for medical workers in their daily work, we can effectively control the occurrence of nosocomial infections and crossinfections and reduce the rate of underreporting by improving the service ability and level of medical workers and promoting their all-round commitment to their work [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…ere were no cases of missed diagnosis or underreporting of infected patients, and no cases of nosocomial infection or cross-infection during the implementation of the normalized management model. By strengthening skills training and psychological interventions for medical workers in their daily work, we can effectively control the occurrence of nosocomial infections and crossinfections and reduce the rate of underreporting by improving the service ability and level of medical workers and promoting their all-round commitment to their work [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that these AgNP colloids have excellent photocatalytic activity and are capable of producing reactive oxygen species (ROS) under visible light irradiation. In general, ROS have broad-spectrum biocidal effects and also play an important role in the orchestration of the wound healing response, since they act as secondary messengers to immunocytes and nonlymphoid cells, regulating the angiogenesis at the wound site. − …”
Section: Introductionmentioning
confidence: 99%
“…Reporter gene expression In living subjects, for studying the magnitude, time variation, and location of reporter gene expression, an improved PET reporter gene tk (HSV1-sr39 thymidine kinase), and rl (Renilla luciferase, a bioluminescence optical reporter gene) are used [112] Assessing cell signaling pathways NanoLuc luminescence has been documented as a tool for detecting both the overall levels of native target proteins and phosphorylation in unaltered cells through immunodetection [113] Bioluminescence-induced photo-uncaging of small molecules Te NanoLuc-Halotag chimera protein (H-Luc) induces BRET to a coumarin substrate, activating the coumarin's excited state. Tis activation, in turn, initiates hydrolysis, leading to the release of a caged target molecule [114] Bioluminescence-based photodynamic therapy (PDT) Self-luminescent photodynamic therapy systems are used with potentials against viral infections [115] Table 4: Continued.…”
Section: Referencesmentioning
confidence: 99%